اتجاهات معلمي التربية الرياضية نحو دمج التلاميذ ذوي الإعاقة مع أقرانهم غير المعاقين بالمدارس الحكومية - قطب، أحمد مصطفى أحمد (جامعة حلوان - كلية التربية الرياضية للبنين, 2022)
يهدف البحث إلى التعرف على اتجاهات معلمي التربية الرياضية نحو دمج التلاميذ ذوي الإعاقة مع أقرانهم غير المعاقين في المدارس الحكومية، حيث أستخدم الباحث المنهج الوصفي نظر لملائمته لطبيعة البحث، ويتمثل مجتمع البحث من معلمين ومعلمات التربية الرياضية في المدارس، حيث بلغ عددهم (1922) معلما ومعلمة، حيث تم اختيار عينة البحث بالطريقة العشوائية من معلمين ومعلمات التربية الرياضية، وتكونت عينة الدراسة من (330) معلما ومعلمة من أفراد مجتمع الدراسة الأصلي موزعين على ست متغيرات أساسية (الجنس، المؤهل الدراسي، الدورات التدريبية، سنوات الخبرة، المرحلة التدريسية، وجود إعاقة داخل العائلة)، وكانت من أهم الاستنتاجات وجود فروق دله إحصائيا بين الذكور والإناث في المكون المعرفي لصالح الذكور، والمكون الوجداني لصالح عينة الإناث، كما توجد فروق غير داله إحصائيا في كلا من متكونات الاتجاهات الثلاثة وفقا لمتغير المؤهلات الدراسية المختلفة، وتوجد فروق داله إحصائيا بين عينة البحث الغير حاصلة على دورات تدريبية وعينة البحث الحاصلة على دورة تدريبية واحدة لصالح عينة البحث الغير الحاصلة على دورات تدريبية، وعينة البحث الحاصلة على دورة تدريبية واحدة فقط والحاصلة على أكثر من دورة تدريبية لصالح عينة البحث الحاصلة على أكثر من دورة تدريبية. وتوجد فروق داله إحصائيا بين عينة البحث التي لديها خبرة أقل من 5 سنوات وعينة البحث التي لديها خبرة (5: 10) سنوات ولصالح عينة البحث التي لديها خبرة أقل من 5 سنوات، وتوجد فروق داله إحصائيا بين عينة البحث التي تدرس لمرحلة الابتدائي وبين عينة البحث التي تدرس لمرحلة الثانوي ولصالح عينة البحث التي درس لمرحلة الابتدائي، كما توجد فروق غير داله إحصائيا بين وجود إعاقة داخل الأسرة في كلا من مكونات الاتجاه الثلاثة. ومن أهم التوصيات التي يوصي بها الباحث أن تتبنى وزارة التربية والتعليم برامج تعليمية مدمجة تخدم كافة التلاميذ المشاركين داخل حصص التربية الرياضية، وتقوم وزارة التربية والتعليم بتوفير الظروف المكانية والتجهيزات المعدلة التي تساعد جميع التلاميذ داخل حصص التربية الرياضية، وضرورة حث الجهات المعنية بعمل المزيد من دورات تدريبية وورش عمل وندوات لمعلمي التربية الرياضية حول العمل مع الأفراد ذوي الإعاقة. The research aims to identify the attitudes of physical education teachers towards integrating students with disabilities with their non-disabled peers in government schools, where the researcher used the descriptive approach due to its suitability to the nature of the research. The study sample consisted of (330) male and female teachers from members of the original study community distributed on six basic variables (gender, academic qualification, training courses, years of experience, teaching stage, presence of family disability), One of the most important conclusions was the presence of statistically significant differences between males and females in the cognitive component in favor of males, and the emotional component in favor of the female sample, and there are non-statistically significant differences in each of the components of the three trends according to the variable of different academic qualifications, and there are statistically significant differences between the non-accomplished research sample. On training courses and the research sample that obtained one training course in favor of the research sample that did not have training courses, and the research sample that received only one training course and obtained more than one training course in favor of the research sample that received more than one training course. And there are statistically significant differences between the research sample that has experience of less than 5 years and the research sample that has experience (5:10) years, and in favor of the research sample that has experience of less than 5 years. There are statistically significant differences between the research sample that studies for the primary stage and the research sample that studies for the secondary stage and in favor of the research sample that is studied for the primary stage, and there are non-statistically significant differences between the presence of a disability within the family in each of the three components of the trend. One of the most important recommendations recommended by the researcher is that the Ministry of Education adopt integrated educational programs that serve all students participating in physical education classes. Training, workshops and seminars for physical education teachers on working with individuals with disabilities.
Keywords: ذوي الاحتياجات الخاصة -- التربية الرياضية -- الثقافة الرياضية -- المؤسسات التعليمية